2020
DOI: 10.1039/d0mt00030b
|View full text |Cite
|
Sign up to set email alerts
|

Comparative high-throughput analysis of the Trypanosoma cruzi response to organometallic compounds

Abstract: An in-depth, comparative look at the effects of two structurally related organometallic Pd and Pt compounds on the global gene expression pattern of T. cruzi epimastigotes. This parasite is the causative agent of Chagas disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 81 publications
0
24
0
Order By: Relevance
“…Fexinidazole, an NTR-1-activated 5-nitroimidazole pro-drug [ 31 ], has been shown to outperform both benznidazole and nifurtimox as a curative treatment for experimental T. cruzi infections [ 34 ] ( Figure 2 A,B, as example), and a clinical trial to assess efficacy and tolerability against patients with asymptomatic chronic infections has been undertaken [ 35 ]. In addition, there have also been a number of recent studies reporting encouraging preliminary data on the antiparasite activities of other novel nitroaromatics [ 88 ], and of a new generation of diverse organometallic compounds [ 89 , 90 , 91 , 92 ].…”
Section: Progress In Chagas Disease Drug Developmentmentioning
confidence: 99%
“…Fexinidazole, an NTR-1-activated 5-nitroimidazole pro-drug [ 31 ], has been shown to outperform both benznidazole and nifurtimox as a curative treatment for experimental T. cruzi infections [ 34 ] ( Figure 2 A,B, as example), and a clinical trial to assess efficacy and tolerability against patients with asymptomatic chronic infections has been undertaken [ 35 ]. In addition, there have also been a number of recent studies reporting encouraging preliminary data on the antiparasite activities of other novel nitroaromatics [ 88 ], and of a new generation of diverse organometallic compounds [ 89 , 90 , 91 , 92 ].…”
Section: Progress In Chagas Disease Drug Developmentmentioning
confidence: 99%
“…Their effect on some selected molecular targets was studied and omic studies were performed for the most promising pyridine-2-thiolato-1oxide (mpo) compounds. In general, the inclusion of the ferrocene moiety led to interesting effects on the biological profile of the compounds (Rodríguez Arce et al, 2015;Mosquillo et al, 2018a;Mosquillo et al, 2018b;Rivas et al, 2018;Rivas et al, 2019;Rodríguez Arce et al, 2019;Mosquillo et al, 2020;Rivas et al, 2021).…”
Section: Ferrocenyl Derivativesmentioning
confidence: 99%
“…High-throughput omic studies have proved to be powerful tools for going further into the basic biology of parasites like T. cruzi and also for the validation of drug targets (Atwood et al, 2005;Chávez et al, 2017;García-Huertas et al, 2017;Van den Kerkhof et al, 2020). Although these studies have been also used to explore organic drugs action in kinetoplastid parasites, similar studies for metal-based drugs were not reported until part of our group recently performed a high throughput omic study on T. cruzi for the two analogous Pt and Pd organometallic hit compounds [M II (dppf)(mpo)](PF 6 ) (Mosquillo et al, 2018a;Mosquillo et al, 2018b;Mosquillo et al, 2020).…”
Section: Ferrocenyl Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the affected pathways, the biosynthesis of ergosterol was found to be modulated by the compounds. [12][13] Ergosterol is essential for providing structure and function of membranes and the parasite is entirely dependent on these endogenously produced sterols for survival and proliferation. Since the enzymes involved in this metabolic pathway are different to their counterparts in the mammalian host, the set of enzymes that participate in the pathway are recognized as attractive targets for antichagasic drugs discovery.…”
Section: Introductionmentioning
confidence: 99%